Reproductive biology of the endangered wattled curassow (Crax globulosa; Galliformes: Cracidae) in the Juruá River Basin, Western Brazilian Amazonia - Leite, Gabriel Augusto (Journal of Natural History, 2020)
The reproductive biology of Crax globulosa is virtually unknown, this knowledge comprised of only a few anecdotal notes. We found nine nests of Crax globulosa in the middle section of the Juruá River, western Brazilian Amazon, during the dry season. Nests averaged 22.5 m from water and 13.3 m above the ground. We observed two nest types: five made of twigs, leaves and vines, and four within a bromeliad. All nests contained two eggs, but six (67%) were subsequently predated. A female tagged with a transmitter nested twice during the same breeding season. A chick was monitored together with its parents for > 10 months. In addition to hunting and habitat loss, nest predation could be another threat to this endangered species. © 2017 Informa UK Limited, trading as Taylor & Francis Group.